Febrile infection‐related epilepsy syndrome (FIRES) is not caused by SCN1A, POLG, PCDH19 mutations or rare copy number variations - Silke Appenzeller; Ingo Helbig; Ulrich Stephani; Martin Häusler; Gerhard Kluger; May Bungeroth; Stefanie H. Müller; Gregor Kuhlenbäumer; Andreas van Baalen (2012)
Aim Febrile infection‐related epilepsy syndrome (FIRES) is an enigmatic seizure disorder in childhood with an innocuous febrile infection triggering severe and intractable multifocal epilepsy, mostly with status epilepticus. FIRES shares several phenotypic features with epilepsies seen in patients with protocadherin 19 ( PCDH19 ), sodium channel protein type 1 subunit alpha ( SCN1A ), and DNA polymerase subunit gamma‐1 ( POLG ) mutations. The aim of the study was the mutation analysis of these prime candidate genes in a cohort of patients with FIRES. Additionally, given that rare copy number variations (CNVs) have recently been established as important risk factors for epilepsies, we performed a genome‐wide CNV analysis. Method We analysed the protein coding region, including splice sites of the three candidate genes in 15 patients (eight males, seven females) with FIRES (age at onset 3–15y, median 6) using Sanger sequencing. Inclusion criteria were a status epilepticus without identifiable cause and a preceding febrile infection in previously healthy children. In addition, we performed genome‐wide human single‐nucleotide polymorphism 6.0 arrays in a subset of 10 patients to identify pathological CNVs. Results We could not identify the most likely pathogenic mutations or CNVs in FIRES. Interpretation Mutations in PCDH19 , SCN1A , POLG , or CNVs are not responsible for FIRES.